The Influence of Interactive Context on Prelinguistic Vocalizations and Maternal Responses. Issue 3 (2nd July 2016) - Gros-Louis, Julie; West, Meredith J.; King, Andrew P.
ABSTRACT: Many studies have documented influences of maternal responsiveness on cognitive and language development. Given the bidirectionality of interactions in caregiver-infant dyads, it is important to understand how infant behavior elicits variable responses. Prior studies have shown that mothers respond differentially to features of prelinguistic vocalizations that reflect phonological complexity; however, studies have also found that maternal responses vary as a function of interactive contexts. Thus, it is important to examine how infant phonological features and social context interact to influence maternal responsiveness because language development occurs in social interactions and moment-to-moment behaviors influence development. In the current study, we examined how maternal responses vary relative to infant vocal production and interactional context: puppet play, toy play, and book reading. Infants produced more syllable-like, consonant-vowels (CV) than vowel-like sounds (V) during book reading. Mothers responded to proportionally more CV vocalizations during book reading and puppet play than during toy play; however, it was only during book reading that mothers responded to CV sounds more than V sounds. Overall, mothers responded to CV sounds with imitations/expansions significantly more than other response types. Examining responses within contexts, however, acknowledgments were the most frequent response type, with naming responses during book reading and questions in the puppet context also occurring frequently. Therefore, maternal responses varied relative to both vocal characteristics and context, suggesting key variables in social interactions that may support language development.